Efektivitas Metode Bernyanyi Pesair terhadap Hasil Belajar Materi Siklus Air pada Siswa SDN Sukorame 2 Kediri - Amalia, Kharisma Ismu; Nurmilawati, Mumun; Santi, Novi Nitya (Efektor, 2024)
The effectiveness of a learning method is a measure of the level of success that has been achieved from using a particular learning method and in accordance with the planned learning objectives. This research aims to determine the effectiveness of the sea singing method in class 5 water cycle material at SDN Sukorame 2 Kediri. The research method used is quantitative descriptive. The analysis technique used is the Independent sample T-test (unpaired T test). The instrument used was multiple choice questions, totaling 10 questions. Based on the results of the research and discussion regarding the effectiveness of the sea singing method on the water cycle material, it can be concluded that the use of the sea singing method can improve student learning outcomes on the water cycle material. This can be seen based on the Independent sample T-test which shows that the sig (2-tailed) value is <0.05, which means that H0 is rejected and Ha is accepted, and there are differences in student learning outcomes using the pesair singing method.